A multicenter study of oral malignant tumors from Thailand - Dhanuthai K. (2017)
© 2016 Journal of Oral and Maxillofacial Pathology | Published by Wolters Kluwer - Medknow. Background: Oral malignant tumors in Thailand have not been extensively studied. Hence the following study was conducted. Aims: To determine the prevalence and clinicopathologic data of the oral malignant tumors from Thailand. Subjects and Methods: Biopsy records of the Oral Pathology Department, Chulalongkorn University; Department of Oral Biology and Diagnostic Sciences, Chiang Mai University; Department of Oral Diagnosis, Khon Kaen University and Department of Stomatology, Prince of Songkla University, were reviewed for lesions diagnosed in the category of oral malignant tumors from 2005-2014. Demographic data and site of the lesions were collected. Statistical Analysis Used: Data were analyzed by descriptive statistics using SPSS software version 17.0. Results: Of the 22,639 accessioned cases, 1411 cases (6.23%) were diagnosed as oral malignant tumors. The mean age of the patients was 59.13 ± 17.32 years. A total of 651 cases (46.14%) were diagnosed in males, whereas 759 cases (53.79%) were diagnosed in females. The male-to-female ratio was 0.86:1. The sites of predilection for oral malignant tumors were the gingiva, followed by tongue and alveolar mucosa. The three most common oral malignant tumors in the descending order of frequency were squamous cell carcinoma, non-Hodgkin lymphoma and mucoepidermoid carcinoma. Conclusions: This study provides extensive data on the oral malignant tumors from several university biopsy services located in virtually all parts of Thailand. The data from the present study show some similarities with previous studies; however, differences such as gender and site of predilection still exist.